IELTS reading test - McCarter, Sam.; Ash, Judith; Nguyễn Thành Yến (Tp.HCM : Nxb Tp.HCM, 2002)
Reading test 1; Reading test 2; Reading test 3; Reading test 4; Reading test 5; Reading test 6; Reading test 7; Reading test 8; Reading test 9; Reading test 10; Key; Appendix.
Keywords: Anh ngữ; English language; IELTS; Reading test; English language -- Study and teaching